2022
DOI: 10.3390/ijerph19137672
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Gender and the Specificity of Sports Activities on the Performance of Body Balance for Students of the Faculty of Physical Education and Sports

Abstract: A sense of balance is required in sports activities, conditioning the quality of movements and physical performance. (1) The purpose of the study is to investigate the influence of gender and the specificity of sports activities on body balance. The investigated participants are 157 students of the Faculty of Physical Education and Sports/Bachelor’s degree: 109 men (age = 20.49 ± 2.03, body mass index, BMI = 22.96 ± 3.20), and 48 women (age = 20.21 ± 1.51, BMI = 21.05 ± 2.78). (2) Design: Cross-sectional study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 90 publications
0
3
0
Order By: Relevance
“…In general, athletes are superior to non-athletes in balance performance ( Davlin, 2004 ). More specifically, athletes of both team and individual sports demonstrate better body balance over the group of non-athletes ( Mocanu et al, 2022 ). Lateral CoP deviation is also lower in individuals with moderate than low physical activities ( Onofrei and Amaricai, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…In general, athletes are superior to non-athletes in balance performance ( Davlin, 2004 ). More specifically, athletes of both team and individual sports demonstrate better body balance over the group of non-athletes ( Mocanu et al, 2022 ). Lateral CoP deviation is also lower in individuals with moderate than low physical activities ( Onofrei and Amaricai, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…In certain sports, women can sometimes outperform men's abilities/achievements. Study Mocanu et al (2022) found that women outperformed men in most sports activities involving balance tests. On the other hand, learning motivation factors can also influence students' PE learning outcomes.…”
Section: Discussionmentioning
confidence: 97%
“…Impairments to the balance and postural stability likely contribute to the increased risk of falls and fractures in patients with Parkinson's disease [8]. Moreover, the maintenance of balance is not only important in daily activities of living, but also in competitive sports activities [9].…”
Section: Introductionmentioning
confidence: 99%